Genetic variation of wild tiger grouper (Epinephelus fuscoguttatus) obtained from Kedah, Malaysia - Waludi, Shaidatul Nadia; Phang, Ing Chia; Mukai, Yukinori (2015)
The genetic variability among individuals of wild tiger grouper (Epinephelus fuscoguttatus) obtained from Kedah, Malaysia was examined by using random amplified polymorphic DNA (RAPD). Five samples of tiger grouper from FRI Pulau Sayak, Kedah, Malaysia were reared in Institute of Oceanography and Maritime Studies (INOCEM), Kampong Cherok Paloh, Pahang, Malaysia. The genomic DNA was extracted by using Qiagen Blood and Tissue kit. A total 155 of RAPD fragments was amplified. 87 polymorphic fragments (56.1%) with size ranging from 200 to 3000bp were scored. Low polymorphism percentage indicates of low genetic variation among the individuals of wild tiger grouper that caused by the small population size that could lead to loss of genetic biodiversity.